АССОЦИАЦИЯ ПОЛИМОРФИЗМА G(5557)A ATM ГЕНА С ФАКТОРОМ РАДИАЦИОННОГО ОБЛУЧЕНИЯ В КАЗАХСТАНСКИХ ПОПУЛЯЦИЯХ (Experimental biology, 2015)
In the article were shown results of the research directed on revealing of association of ATM gene polymorphic variant G (5557) A with the factor of a radiation in the Kazakhstan populations, representing families from area of action Semipalatinsk nuclear polygon, and Chernobyl accident consequences liquidators, inhabitants of Semipalatinsk were presented. The matched cohorts from ecologically favorable Almaty area regions were investigated as a control. The association between the radiation factor and heterozygote carrying of polymorphism АТМ G(5557)A was revealed. It is established that indicators of relative risk in population of liquidators of Chernobyl accident consequences were above than the same rates in population of families living around the Semipalatinsk nuclear polygon area. This implies the facts that the dose of the irradiation received by the cohort of liquidators of Chernobyl accident consequences were considerably higher and this cohort expresses the bad medical status, including the development of cancer,cardiovascular and autoimmune pathologies.
Keywords: Semipalatinsk nuclear polygon